Sketch of the life and discoveries of Robert Campbell, chief factor of the Hon. Hudson's Bay Company [electronic resource] - Bryce, George, 1844-1931; Historical and Scientific Society of Manitoba. (Winnipeg : Manitoba Free Press, 1898)
At head of title: Transaction No. 522, April 14, 1898. The Historical and Scientific Society of Manitoba. Electronic reproduction. Mode of access: Internet. 44